Public-Private Partnerships and the Healthcare Sector Performance in Kenya - Munyoki, Michael; Nasieku, Tabitha (Advances in Social Sciences Research Journal, 2021)
Healthcare is one of the fundamental development agenda to any nation and its adequate provision in an accessible, quality and sustainable manner is the supreme responsibility of the state. However, the burden of healthcare cannot be met by the government alone, but requires substantial investment from the private sector as well. This article reviews the existing empirical literature to examine the contribution of private investment on the healthcare sector performance in Kenya. Existing evidence shows that there is minimal private-public partnership in the health sector in Kenya. The main factors inhibiting private-public partnership investment in the sector were attributed to the uncertainty associated with universal healthcare. Further, the scheme is characterised by an overall lack of transparency and accountability surrounding contracts, costing and allocations with many of the safeguards against these kinds of challenges blatantly ignored by several actors and in turn raising issues of accessibility for citizens. Also, private sector credit and political regimes have a negative but significant influence on private investments generally.